Coordination Council on the Problem of Forensic Expertise under the Ministry of Justice of Ukraine: Composition, Tasks, Authorities, Rights - Martynenko, Natalia (Theory and Practice of Public Administration, 2024)
In order to improve and establish uniformity in the scientific and methodological provision of forensic examinations, significant changes have been proposed to the Regulations on the Coordination Council on Forensic Examination Problems under the Ministry of Justice of Ukraine regarding the composition of the Coordination Council, expansion of its powers, definition of tasks and rights. Differences in the terminology of the Law of Ukraine “On Forensic Expertise” and the Regulations on the Coordinating Council on Forensic Expertise Issues under the Ministry of Justice of Ukraine are noted. Attention was drawn to the limitation of the right of judicial experts, who are not employees of state specialized institutions and members of public organizations of judicial experts, to be elected to the Coordinating Council, which can be solved by introducing representation from the self-governing body of judicial experts. The need to adopt a law that will take into account the issue of self-governance of judicial experts is noted. It is noted that the Regulations on the Coordinating Council on Forensic Expertise Issues under the Ministry of Justice of Ukraine do not specify the powers of the chairman, executive secretary and members of the Coordinating Council. Lists of powers of the chairman, executive secretary and members of the Coordination Council are proposed. It is pointed out the need to take into account the fact that the gender dimension should become an integral part of the process of development, implementation, monitoring, evaluation of policies and activities in the field of forensic expert activity when forming the composition of the Coordination Council and in its activities. The powers of the Coordination Council have been analyzed. It is pointed out that the list of powers of the Coordinating Council does not mention the coordination of standardization in the field of forensic expertise. It is proposed to supplement the powers of the Coordination Council with the following: analysis of the state of affairs and the causes of problems in the process of implementing state policy in the field of forensic expert activity; development of proposals for determining general approaches to scientific and methodological support of forensic expert activity, professional training and specialization of experts; development of scientifically based standards of expert methods for all classes (types) of forensic examinations, etc. The need to plan the work of the Coordinating Council is indicated – defining the period for which the plan is drawn up; grounds; order of drawing up, consideration at meetings, approval of the plan. It is proposed to enshrine in the Regulations on the Coordinating Council on Forensic Expertise Issues under the Ministry of Justice of Ukraine the obligation to implement the decisions of the Coordinating Council, made within its competence, by the interested bodies represented in it.